2012
DOI: 10.1029/2012jd017598
|View full text |Cite
|
Sign up to set email alerts
|

Planetary boundary layer heights from GPS radio occultation refractivity and humidity profiles

Abstract: [1] The height of the planetary boundary layer (PBL) is an important parameter that relates to the various processes associated with the PBL. In this paper, we use Global Positioning System radio occultation (GPSRO) measurements to derive a global climatology of PBL heights. Utilizing the strength of GPSRO in capturing fine vertical structures, the top of the PBL is defined to be the height at which the vertical gradient of the refractivity or water vapor partial pressure is minimum, corresponding to the heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 46 publications
7
153
0
Order By: Relevance
“…The h can be estimated as the level of the minimum vertical gradient of relative humidity (h RH ) or specific humidity (h q ) with a significant reduction in atmospheric moisture (Ao et al, 2008;Seidel et al, 2010). Additionally, atmospheric refractivity (N), which combines the information of temperature and humidity (defined in Eq.…”
Section: Comparison Of the Existing Methods To Determine Hmentioning
confidence: 99%
“…The h can be estimated as the level of the minimum vertical gradient of relative humidity (h RH ) or specific humidity (h q ) with a significant reduction in atmospheric moisture (Ao et al, 2008;Seidel et al, 2010). Additionally, atmospheric refractivity (N), which combines the information of temperature and humidity (defined in Eq.…”
Section: Comparison Of the Existing Methods To Determine Hmentioning
confidence: 99%
“…Several studies have utilized such features in RO refractivity profile for detecting the ABL height by locating the height of maximum refractivity gradient (MRG) in GPS RO profiles with some differences in algorithm implementation (e.g., Sokolovskiy et al, 2006;Ao et al, 2008;Basha and Ratnam, 2009;Guo et al, 2011;Ao et al, 2012). For a well-defined ABL (e.g., over VOCALS region), the refractivity gradient method is consistent with other conventional definitions (e.g., gradient method based on temperature or humidity profiles) (Basha and Ratnam, 2009;Seidel et al, 2010;von Engeln and Teixeira, 2011;Ao et al, 2012).…”
Section: Typical Abl Structure Over Vocals Regionmentioning
confidence: 97%
“…It is important to note that the implementation of the open-loop tracking technique on the COS-MIC RO receivers significantly improves the quality of RO soundings in the moist ABL, as compared with the early GPS RO missions that used phase-locked loop (PLL) tracking technique (Sokolovskiy 2001;Ao et al, 2009). Several studies have demonstrated the values of RO soundings in detecting the ABL height (e.g., Sokolovskiy et al, 2006;Sokolovskiy et al, 2007;Ao et al, 2008;Basha and Ratnam, 2009;Guo et al, 2011;Ao et al, 2012). However, probing the ABL interior with RO remains to be challenging.…”
Section: F Xie Et Al: Advances and Limitations Of Abl Observations mentioning
confidence: 99%
“…A few studies have been done by using Global Positioning System radio occultation (GPS RO) measurements (Ratnam and Basha, 2010;Guo et al, 2011;Ao et al, 2012) or Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) (McGrath-Spangler and Denning, 2013). GPS RO provides a valuable global view of the height-resolved refractivity or moisture structure of ABL.…”
Section: Introductionmentioning
confidence: 99%